1995
DOI: 10.1063/1.468817
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy of size-selected transition metal clusters: Fe−n, n=3–24

Abstract: A higher resolution magnetic bottle photoelectron spectrometer for the study of the electronic structure of size-selected metal clusters is presented. The initial study on Fe n Ϫ ͑nϭ3-24͒ is reported at a photon energy of 3.49 eV. The photoelectron spectra of these clusters exhibit sharp features throughout the size range. The spectra for Fe 3-8Ϫ show large size dependence with many resolved features. The spectra for Fe 9-15 Ϫ exhibit some similarity with each other, all with a rather sharp feature near the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
258
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 403 publications
(264 citation statements)
references
References 64 publications
5
258
0
1
Order By: Relevance
“…The tubular structure gives rise to 20 strong peripheral B-B bonds, more than any planar isomers. Furthermore, although -bonding in smaller B clusters indeed provides additional stability to the planar structure, our previous work on B 10 to B 15 revealed that in larger clusters the orbitals tend to fragment (localize) in different parts of the 2D structures (14), weakening the contributions of the -bonding to the stability of planar isomers and hinting possible 2D-to-3D transitions with increasing cluster sizes. On the other hand, despite the curvature there is still considerable -bonding in the tubular structure, similar to that in fullerenes or carbon nanotubes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The tubular structure gives rise to 20 strong peripheral B-B bonds, more than any planar isomers. Furthermore, although -bonding in smaller B clusters indeed provides additional stability to the planar structure, our previous work on B 10 to B 15 revealed that in larger clusters the orbitals tend to fragment (localize) in different parts of the 2D structures (14), weakening the contributions of the -bonding to the stability of planar isomers and hinting possible 2D-to-3D transitions with increasing cluster sizes. On the other hand, despite the curvature there is still considerable -bonding in the tubular structure, similar to that in fullerenes or carbon nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments were carried out by using a magnetic-bottle time-of-flight PES apparatus equipped with a laser vaporization supersonic cluster source (15,17). B n Ϫ cluster anions were produced by laser vaporization of a disk target made of enriched 10 B isotope (99.75%) in the presence of a helium carrier gas and were analyzed with a time-of-flight mass spectrometer.…”
Section: Pesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The MAu 16 − ͑M =Ag,Zn,In͒ clusters were produced by laser vaporization of Au/ M composite disk targets containing about 7% Ag, 8% Zn, and 4% In, respectively. Negatively charged clusters were extracted from the cluster beam and analyzed using a time-of-flight mass spectrometer.…”
mentioning
confidence: 99%